Pengaruh Variasi Media Quenching pada Solution Treatment Paduan Al–Si Hasil Remelting piston terhadap Kekerasan dan Struktur Mikro - Titiek Deasy Saptaryani; Muhammad Munawir Lasiyono (Infotekmesin, 2026)
Recycled aluminum–silicon (Al–Si) alloys produced from remelted automotive pistons are increasingly utilized in the casting industry because of their cost-effectiveness, recyclability, and environmental benefits. However, the remelting process may degrade material quality through microstructural changes, porosity formation, and deterioration of mechanical properties. Studies investigating the influence of different quenching media on remelted Al–Si piston alloys remain limited. The novelty of this study lies in evaluating the relationship between quenching media, microstructural evolution, and hardness characteristics of remelted Al–Si piston alloys. This study aimed to investigate the effect of different quenching media after solution treatment on the hardness and microstructure of remelted Al–Si alloys. Used automotive pistons were remelted, cast into metal molds, and machined into standard test specimens. The specimens were heated from room temperature to 550 °C in approximately 30 min, held at 550 °C for 90 min, and quenched in water, oil, or air. Hardness was evaluated using the Brinell hardness test, while the microstructure was examined by optical microscopy. The highest hardness was obtained in the specimen without quenching (63.3 HB), followed by water quenching (62.6 HB), oil quenching (59.6 HB), and air cooling (51.6 HB). Water quenching produced a finer and more homogeneous distribution of silicon particles than oil and air cooling. These findings provide a scientific basis for selecting an appropriate quenching medium to optimize the heat treatment of recycled Al–Si alloys for sustainable casting applications.